Long-Term Performance and Durability of Heat-Treated Alkali-Activated Slag Mortar Containing Silica Fume - Naser Sameti; Ebrahim Ghiasvand; Ehsanollah Zeighami; Seyyed Mohammad Mirhosseini (Advances in Civil Engineering)
This study aimed to investigate the combined influence of heat curing and partial replacement of silica fume on the long-term behavior of alkali-activated slag (AAS) mortar. Silica fume replacement levels of 0%, 5%, and 10% were examined, with curing conducted at temperatures of 23 ± 2 and 80°C. The alkaline activator consisted of sodium hydroxide solution (4 M) mixed with sodium silicate in a 3 : 1 ratio by weight. The performance of the fabricated specimens was evaluated through compressive strength testing, mass change analysis, X-ray diffraction, and scanning electron microscopy. Heat treatment resulted in improved performance of AAS mortars, while silica fume replacement also positively influenced mortar behavior. Notably, the 5% replacement rate yielded the most favorable outcomes. However, it was observed that the long-term compressive strength of AAS mortar specimens decreased significantly. Potential adverse factors contributing to this decline were discussed. Furthermore, the durability of mortar samples exposed to adverse conditions was investigated. Results indicated that the combined use of heat curing and a 5% silica fume replacement level produced the best overall performance.